Population cost-effectiveness of the Triple P parenting programme for the treatment of conduct disorder: an economic modelling study - Sampaio, Filipa (Eur Child Adolesc Psychiatry, 2017)
Parenting programmes are the recommended treatments of conduct disorders (CD) in children, but little is known about their longer term cost-effectiveness. This study aimed to evaluate the population cost-effectiveness of one of the most researched evidence-based parenting programmes, the Triple P—Positive Parenting Programme, delivered in a group and individual format, for the treatment of CD in children. A population-based multiple cohort decision analytic model was developed to estimate the cost per disability-adjusted life year (DALY) averted of Triple P compared with a ‘no intervention’ scenario, using a health sector perspective. The model targeted a cohort of 5–9-year-old children with CD in Australia currently seeking treatment, and followed them until they reached adulthood (i.e., 18 years). Multivariate probabilistic and univariate sensitivity analyses were conducted to incorporate uncertainty in the model parameters. Triple P was cost-effective compared to no intervention at a threshold of AU$50,000 per DALY averted when delivered in a group format [incremental cost-effectiveness ratio (ICER) = $1013 per DALY averted; 95% uncertainty interval (UI) 471–1956] and in an individual format (ICER = $20,498 per DALY averted; 95% UI 11,146–39,470). Evidence-based parenting programmes, such as the Triple P, for the treatment of CD among children appear to represent good value for money, when delivered in a group or an individual face-to-face format, with the group format being the most cost-effective option. The current model can be used for economic evaluations of other interventions targeting CD and in other settings. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00787-017-1100-1) contains supplementary material, which is available to authorized users.